2015
DOI: 10.1016/j.coviro.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem simplification, biodiversity loss and plant virus emergence

Abstract: Plant viruses can emerge into crops from wild plant hosts, or conversely from domestic (crop) plants into wild hosts. Changes in ecosystems, including loss of biodiversity and increases in managed croplands, can impact the emergence of plant virus disease. Although data are limited, in general the loss of biodiversity is thought to contribute to disease emergence. More in-depth studies have been done for human viruses, but studies with plant viruses suggest similar patterns, and indicate that simplification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 85 publications
1
111
0
1
Order By: Relevance
“…One study using White clover mosaic virus (WClMV) on a variety of white clover genotypes found that the virus had a negative impact on all genotypes but the degree of impact varied greatly from one genotype to another, providing empirical evidence that a virus in the environment can effect the genotypic diversity or G X E (vanMölken and Stuefer, 2011). Hence while host diversity can impact the incidence and outcome of virus infection in plants (Roossinck and García-Arenal, 2015), viruses also can impact the degree of host diversity.…”
Section: Viruses and Host Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study using White clover mosaic virus (WClMV) on a variety of white clover genotypes found that the virus had a negative impact on all genotypes but the degree of impact varied greatly from one genotype to another, providing empirical evidence that a virus in the environment can effect the genotypic diversity or G X E (vanMölken and Stuefer, 2011). Hence while host diversity can impact the incidence and outcome of virus infection in plants (Roossinck and García-Arenal, 2015), viruses also can impact the degree of host diversity.…”
Section: Viruses and Host Evolutionmentioning
confidence: 99%
“…Virus incidence is greatest in the cultivated stands with low diversity, and lowest in the wild stands; hence plant population variation is critical to keeping virus levels low (Rodelo-Urrego et al, 2013). The link between biodiversity and virus disease incidence has been suggested for some time but few actual case studies have been done (Roossinck and García-Arenal, 2015). In the chiltepin, in addition to the lower incidence of virus infection, the level of disease in the infected wild plants is lower than in the cultivated plants (Rodelo-Urrego et al, 2013).…”
Section: Viruses In Domestic and Managed Plant Communitiesmentioning
confidence: 99%
“…There is evidence that wild flora acts as a reservoir of viruses causing significant losses in nearby crops and vice versa [17]. However, information about viruses in wild species is still quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…This includes the introduction of hosts, viruses (and vectors), often by human activity, in areas where they were not present before. Other factor facilitating new contacts is ecosystem simplification [81], characterized by reduced species diversity in agricultural compared to natural ecosystems, a concomitant reduction in the genetic diversity of crops compared to wild populations and a higher host density. A second phase consists on the evolutionary process of virus adaptation to the new host or environment to the point that new infections and transmission in the new host is ensured, making between-host transmission independent from the original reservoir.…”
Section: Dynamics Of Genetic Diversity and Structure Of Plant Virus Pmentioning
confidence: 99%